Endoscopic ultrasound in pediatric population: a comprehensive review of the literature - Bizzarri, Barbara; Nervi, Giorgio; Ghiselli, Alessia; Manzali, Elisabetta; Di Mario, Francesco; Leandro, Gioacchino; Gaiani, Federica; Kayali, Stefano; de' Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: Endoscopic ultrasonography (EUS) with or without fine needle aspiration/biopsy (FNA/B) is a well-established diagnostic tool in adults for the evaluation and management of gastrointestinal (GI) tract disorders. Its use in children is still limited as well as literature in pediatric age is limited, although the application of EUS is now increasing. The present article aims to review the current literature about EUS indication, accuracy and safety in pediatric age. Methods: Electronic literature searches were conducted using Pubmed, Medline, Embase, and the Cochrane Central Register of Controlled Trials using the word pediatric endoscopic ultrasound, pediatric pancreaticobiliary AND/OR EUS, pediatric EUS technique. Main patients and procedures characteristics were analyzed. The primary endpoint was the indication of EUS. Secondary endpoints were the accuracy of the technique and the incidence of complications. Results: Data were extracted from 19 articles. A total of 571 patients were investigated, with a median age of 12,7 years. A total of 634 EUS procedures were performed. The majority of EUS procedures investigated the pancreaticobiliary tract (77,7%). Most studies showed a high positive impact on management with a median value of 81,7%. No major complications were reported. Five studies reported minor complications with a median value of 2%. Conclusions: EUS is safe and has a significant role in the diagnosis of pancreaticobiliary and GI diseases even in children, with a high therapeutic success. An increasing EUS utilization by pediatric gastroenterologists is expected and offering dedicated EUS training to some selected pediatric gastroenterologists might be indicated.